(untitled) (Journal of Additive Manufacturing Technologies, 2023)
In this study, electromagnetic characterization of 3D printed metamaterials manufactured by using conductive paint is carried out in terms of their absorption behavior. The samples have been prepared in sizes to fit waveguide setup in the frequency range of 12-18 GHz. 3D printing technique was used to prepare the substrate of the design while conductive paint and copper tape were used for the conductive parts of the structure including the metamaterial resonator and the ground plane. For electromagnetic characterization of the design, different thickness of substrate layers, various raster orientation (0°, ±45° and ±90°), different infill densities have been simulated and experimentally tested in terms of their effects on absorption behavior. In addition, conductivity of the paint was improved by adjusting its formulation and the resulting absorption behaviors have been compared with copper tape using the same metamaterial dimensions. Using 3D printing technology along with conductive paint rather than solid conductors in manufacturing electromagnetic absorbers will provide the possibility of producing flexible and non-planar electromagnetic absorber structures in desired frequency ranges. The design can be easily adopted to different frequencies and this technique can be used to design wideband metamaterial absorbers using 3D layered structures.